2018
DOI: 10.1016/j.toxrep.2017.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Malathion, an organophosphate insecticide, provokes metabolic, histopathologic and molecular disorders in liver and kidney in prepubertal male mice

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 54 publications
20
53
0
3
Order By: Relevance
“…As a result, the amount of these parameters in the blood is directly associated with the amount of liver injured. The results reported in this study are in agreement with previous studies, which indicated that exposure to malathion and other pesticides induced severe adverse biochemical alterations that affect the functional and structural integrity of the liver tissues in experimental animals (Al-Attar, 2010; Al-Attar, 2015; Kasmi et al, 2018;Selmi et al, 2018;Aboubakr et al, 2019;Jalili et al, 2019;Khalifa and Alkhalf, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As a result, the amount of these parameters in the blood is directly associated with the amount of liver injured. The results reported in this study are in agreement with previous studies, which indicated that exposure to malathion and other pesticides induced severe adverse biochemical alterations that affect the functional and structural integrity of the liver tissues in experimental animals (Al-Attar, 2010; Al-Attar, 2015; Kasmi et al, 2018;Selmi et al, 2018;Aboubakr et al, 2019;Jalili et al, 2019;Khalifa and Alkhalf, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The present results revealed that the exposure to malathion led to the decline of serum total protein level, while the levels of serum glucose, triglycerides and cholesterol were significantly enhanced. These results are consistent with previous studies which indicated that exposure to malathion and other pesticides induced severe disturbance of proteins, carbohydrates and lipids metabolism (Al-Attar, 2015;El-Beih et al, 2017;Selmi et al, 2018;Khalifa and Alkhalf, 2019). The decline of serum total protein indicates the presence of para proteins or decreased antibody production.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[12] Kidney is the major organ for metabolism and disposal of malathion through urine. [13] The primary or secondary disposal of some drugs and toxins during a progressive trend usually leads to chronic renal disorders. [14] Resveratrol is a plant-derived polyphenolic phytoalexin that is produced by stilbene synthase enzyme in response to environmental stresses such as climate change, exposure to heavy metals, and infectious agents.…”
mentioning
confidence: 99%
“…The unregulated use of OPPs and their application over large agricultural and urban areas, has caused severe environmental pollution and potential health hazards (Sodhi et al, 2008). Particularly, malathion [O,Odimethyl-S-(1,2-dicarcethoxyethyl) phosphorodithioate] is a widely used OPP habitually used to eradicate ectoparasites, household insects, to conserve stored grain and to eliminate disease-inducing arthropods (Selmi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%